2012
DOI: 10.1890/11-1838.1
|View full text |Cite
|
Sign up to set email alerts
|

Both host plant and ecosystem engineer identity influence leaf‐tie impacts on the arthropod community of Quercus

Abstract: Many insect herbivores build shelters on plants, which are then colonized by other arthropod species. To understand the impacts of such ecosystem engineering on associated species, the contributions of ecosystem engineer and host-plant identities must be understood. We investigated these contingencies at the patch scale using two species of leaf-tying caterpillars, which vary in size and tie construction mode, on eight species of oak (Quercus) trees, which vary in leaf size and leaf chemistry. We created three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
0
24
2
2
Order By: Relevance
“…However, it disappeared completely in the spectrum of DOPNP, and the disappearance of the characteristic absorption band of OAH indicates that the final product was obtained successfully. 16,23 that is because the ACH 2 A protons (c) and (d) are at both sides of the six-membered heterocyclic (see in Fig. 2), and the different environment conditions lead to the two unequivalent protons (c) and (d).…”
Section: Resultsmentioning
confidence: 99%
“…However, it disappeared completely in the spectrum of DOPNP, and the disappearance of the characteristic absorption band of OAH indicates that the final product was obtained successfully. 16,23 that is because the ACH 2 A protons (c) and (d) are at both sides of the six-membered heterocyclic (see in Fig. 2), and the different environment conditions lead to the two unequivalent protons (c) and (d).…”
Section: Resultsmentioning
confidence: 99%
“…within a tree's canopy is an important organizing factor because the species richness of the associated insect herbivore community was determinate. Similarly, Wang et al (2012) using two species of leaf-tying caterpillars Pseudotelphusa quercinigracella and Psilocorsis cryptolechiella found that the presence of leaf ties increased species density and abundance of herbivores, predators, and scavengers, depending on the oak host species (Q. alba, Q. imbricaria, Q. macrocarpa, Q. marilandica, Q. muehlenbergii, Q. velutina, Q. rubra, and Q. stellata). Also, arthropod species composition differed between untied leaves and between ties made by the two leaf-tier species.…”
Section: Biotic Interactionsmentioning
confidence: 97%
“…Larger scales often mean more heterogeneous environments for organisms, and varied environments can lead to the change of biotic interactions (Griffin, Byrnes, & Cardinale 2013). For example, the ecological effects of leaf-rollers can differ between leaf and plant scale (Vieira & Romero 2013;Wang, Marquis, & Baer 2012). On the host plant Solanum lycocarpum, the outcomes of ant-treehopper association are scale-dependent (Moreira & Del-Claro 2005).…”
Section: Introductionmentioning
confidence: 99%